2022
DOI: 10.3389/fphar.2022.891889
|View full text |Cite
|
Sign up to set email alerts
|

Network Pharmacology and Experimental Validation to Explore the Mechanism of Qing-Jin-Hua-Tan-Decoction Against Acute Lung Injury

Abstract: Qing-Jin-Hua-Tan-Decoction (QJHTD), a classic famous Chinese ancient prescription, has been used for treatment of pulmonary diseases since Ming Dynasty. A total of 22 prototype compounds of QJHTD absorbed into rat blood were chosen as candidates for the pharmacological network analysis and molecular docking. The targets from the intersection of compound target and ALI disease targets were used for GO and KEGG enrichment analyses. Molecular docking was adopted to further verify the interactions between 22 compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 110 publications
1
8
0
Order By: Relevance
“…[21,38] Qingjin Huatan decoction could inhibit PMA-induced production of NETs and the results of network pharmacology suggested that NETs may be the mechanism of QJHTD in treating ALI. [15] The previous research results and transcriptomic data suggested that QJHTD might attenuate ALI by inhibiting the formation of NETs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[21,38] Qingjin Huatan decoction could inhibit PMA-induced production of NETs and the results of network pharmacology suggested that NETs may be the mechanism of QJHTD in treating ALI. [15] The previous research results and transcriptomic data suggested that QJHTD might attenuate ALI by inhibiting the formation of NETs.…”
Section: Resultsmentioning
confidence: 99%
“…The KEGG pathway enrichment results showed that QJHTD treated ALI via osteoclast differentiation, TNF, NET formation, and IL-17 signaling pathways. Our previous network pharmacology-based study also revealed that the mechanism of QJHTD in treating ALI involved the formation of NETs, [15] indicating that QJHTD might play a protective role against ALI by inhibiting NETs. The recent studies have shown that a large number of NETs are produced during the progress of ALI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pharmacological studies have shown suppression of TLR4-mediated NF-κB activation ( Zhang et al, 2016 ; Feng et al, 2018 ), downregulation of MMP9 expression ( Zhang et al, 2016 ), inhibition of p-Src in LPS-activated neutrophils and formation of neutrophil extracellular traps (NETs) in Phorbol 12-myristate 13-acetate (PMA)-induced neutrophils ( Xiao et al, 2022 ) in response to traditional Chinese medications containing baicalin.…”
Section: Methodsmentioning
confidence: 99%